Cataract: Advances in surgery and whether surgery remains the only treatment in future - Chen, Xinyi; Xu, Jingjie; Chen, Xiangjun; Yao, Ke (Advances in ophthalmology practice and research, 2021)
Cataract is the world's leading eye disease that causes blindness. The prevalence of cataract aged 40 years and older is approximately 11.8%–18.8%. Currently, surgery is the only way to treat cataracts. From early intracapsular cataract extraction to extracapsular cataract extraction, to current phacoemulsification cataract surgery, the incision ranges from 12 to 3 ​mm, and sometimes to even 1.8 ​mm or less, and the revolution in cataract surgery is ongoing. Cataract surgery has transformed from vision recovery to refractive surgery, leading to the era of refractive cataract surgery, and premium intraocular lenses (IOLs) such as toric IOLs, multifocal IOLs, and extended depth-of-focus IOLs are being increasingly used to meet the individual needs of patients. With its advantages of providing better visual acuity and causing fewer complications, phacoemulsification is currently the mainstream cataract surgery technique worldwide. However, patient expectations for the safety and accuracy of the operation are continually increasing. Femtosecond laser-assisted cataract surgery (FLACS) has entered the public's field of vision. FLACS is a combination of new laser technology and artificial intelligence to replace fine manual clear corneal incision, capsulorhexis, and nuclear pre-fragmentation, providing new alternative technologies for patients and ophthalmologists. As FLACS matures, it is being increasingly applied in complex cases; however, some think it is not cost-effective. Although more than 26 million cataract surgeries are performed each year, there is still a gap in the prevalence of cataracts, especially in developing countries. Although cataract surgery is a nearly ideal procedure and complications are manageable, both patients and doctors dream of using drugs to cure cataracts. Is surgery really the only way to treat cataracts in the future? It has been verified by animal experiments that lanosterol therapy in rabbits and dogs could make cataract severity alleviated and lens transparency partially recovered. Although there is still much to learn about cataract reversal, this groundbreaking work provided a new strategy for the prevention and treatment of cataracts. Although cataract surgery is nearly ideal, it is still insufficient, we expect the prospects for cataract drugs to be bright.